Effect of arbuscular mycorrhizal fungi on the physiological traits and growth of three woody species from a tropical dry forest - Cáceres-Mago, Karla; Cáceres, Alicia; Ávila-Lovera, Eleinis; Tezara, Wilmer (Frontiers in Ecology and Evolution, 2025)
The tropical dry forests (TDFs) of the Macanao Peninsula (Margarita Island, Venezuela) have been severely degraded by open-cast sand mining for over four decades, reducing vegetation cover and disrupting soil biological processes, including those mediated by arbuscular mycorrhizal fungi (AMF). To assess whether enriching native AMF communities can improve plant performance, we evaluated the physiological traits and growth of three woody species (Bulnesia arborea, Caesalpinia mollis and Piptadenia flava) grown for eight months under greenhouse conditions in noninoculated (NI) and inoculated (I) treatments, both using the same non-sterile forest soil to ensure that inoculation represented enrichment of the native AMF community, which reflects realistic restoration scenarios. Species differed markedly in their responses: in B. arborea, AMF enrichment increased net photosynthetic rate and stomatal conductance by 50% and 31%, respectively, and significantly enhanced the maximum rate of RuBisCO carboxylation and biomass accumulation; in C. mollis, inoculation increased CO2-saturated photosynthetic rate but did not affect growth; and in P. flava, inoculated plants showed greater shoot biomass and root length despite no detectable changes in photosynthetic parameters. These species-specific responses suggest that B. arborea may hold potential for future restoration testing in the Macanao Peninsula, and further ecological evaluation is needed before selecting species for restoration.